First occurrence of Parksosauridae in Mexico, from the Cerro del Pueblo Formation (Late Cretaceous; late Campanian) at Las Águilas, Coahuila - Rivera-Sylva, Héctor E.; Stinnesbeck, Wolfgang (Boletín de la Sociedad Geológica Mexicana, 2018)
AbstractThe Las Águilas locality near Porvenir de Jalpa, Coahuila, México, is extremely rich in fossil remains comprising both bones and trackways of several late Campanian dinosaur taxa. Here we present a tooth with an asymmetrically bulged crown and an isolated shallow amphicoelous vertebral centrum. Both are assigned by us to Parksosauridae. The material represents the first occurrence of this enigmatic family in México.Keywords: Cerro del Pueblo Formation; Parksosauridae; Campanian; Coahuila; México